1980
DOI: 10.1152/jappl.1980.49.5.863
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake, acid-base status, and performance with varied inspired oxygen fractions

Abstract: Six subjects rode a bicycle ergometer on three occasions breathing 17, 21, or 60% oxygen. In addition to rest and recovery periods, each subject worked for 10 min at 55% of maximal oxygen uptake (VO2 max) and then to exhaustion at approximately 90% VO2 max. Performance time, inspired and expired gas fractions, ventilation, and arterialized venous oxygen tension (PO2), carbon dioxide tension (PCO2), lactate, and pH were measured. VO2, carbon dioxide output, [H+]a, and [HCO3-]a were calculated. Performance times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
72
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 10 publications
12
72
0
2
Order By: Relevance
“…Therefore the decrease in plasma glutamine concentration from 30 min post-ingestion to the onset of exercise suggests that a significant amount of glutamine entered the muscle (Varnier, Leese, Thompson, & Rennie, 1995). Hence it is likely that in the present study glutamine ingestion The lack of any effect of hyperoxia on plasma lactate concentration during maximal exercise was perhaps not surprising since a number of previous studies have found similar results (Linnarsson et al 1974;Adams & Welch, 1980;Knight et al 1993;Hogan et al 1999;Linossier et al 2000;Savasi et al 2002) suggesting that whilst exercise performance is enhanced in hyperoxia, fatigue occurs at the same intracellular concentrations of potential fatiguing metabolites (H + , AMP, IMP, Pi).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Therefore the decrease in plasma glutamine concentration from 30 min post-ingestion to the onset of exercise suggests that a significant amount of glutamine entered the muscle (Varnier, Leese, Thompson, & Rennie, 1995). Hence it is likely that in the present study glutamine ingestion The lack of any effect of hyperoxia on plasma lactate concentration during maximal exercise was perhaps not surprising since a number of previous studies have found similar results (Linnarsson et al 1974;Adams & Welch, 1980;Knight et al 1993;Hogan et al 1999;Linossier et al 2000;Savasi et al 2002) suggesting that whilst exercise performance is enhanced in hyperoxia, fatigue occurs at the same intracellular concentrations of potential fatiguing metabolites (H + , AMP, IMP, Pi).…”
Section: Discussionmentioning
confidence: 50%
“…In contrast performance was enhanced by ~ 6% in hyperoxia, with a concomitant significant increase in  2 o V  . Hyperoxia has previously been shown to result in enhanced performance during high intensity exercise (Linnarsson, et al 1974;Adams & Welch, 1980;Knight et al 1993;Hogan et al 1999;Richardson et al 1999a,b;Linossier et al 2000). The mechanism by which hyperoxia exerts this effect appears to be via facilitation of oxygen consumption compared to normoxic conditions, resulting in a delay before the accumulation of metabolic by-products (H + , AMP, IMP, Pi) to fatiguing levels (Linnarsson, et al 1974;Adams & Welch, 1980;Knight et al 1993;Hogan et al 1999;Linossier et al 2000;Prieur et al 2006) Glutamine ingestion conferred no main effect on any measured parameter.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In healthy subjects and in patients with peripheral vascular disease, muscle ischaemia is a potent stimulus for improving endurance exercise [36]. Since supplemental oxygen abolishes the desaturation and reduces lactate levels during exercise [4,37], it might also have reduced the training stimulus in these patients.…”
Section: Effects Of Oxygen-supplemented Exercise Trainingmentioning
confidence: 99%
“…This limitation has been attributed to a lowered O 2 partial pressure in arterial blood (Pa O 2 ) reducing arterial O 2 content and O 2 delivery to tissues with critical consequences on muscle metabolism and contraction (1,46). Magnetic nerve stimulation has confirmed the effects of reduced arterial oxygenation on dynamic (12,111) and static (54) exercise-induced alterations in muscle contractility.…”
mentioning
confidence: 99%